2020
DOI: 10.1073/pnas.1907343117
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cumulative prevalence measures of child mortality show heavy burden in sub-Saharan Africa

Abstract: We advance a set of population-level indicators that quantify the prevalence of mothers who have ever experienced an infant, under 5-y-old child, or any-age child die. The maternal cumulative prevalence of infant mortality (mIM), the maternal cumulative prevalence of under 5 mortality (mU5M), and the maternal cumulative prevalence of offspring mortality (mOM) bring theoretical and practical value to a variety of disciplines. Here we introduce maternal cumulative prevalence measures of mortality for multiple ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
1
16
0
2
Order By: Relevance
“…That is, the maximum number of spouses and biological parents and grandparents that could be lost are one, two, and four; few will lose a child, and almost none will lose a grandchild to COVID-19. In situations where mortality concentrates among the young, however, these caps would not apply and there would be substantial heterogeneity in mortality experiences, between people and potentially between epidemiological realities ( 3 ).…”
Section: Sensitivity Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, the maximum number of spouses and biological parents and grandparents that could be lost are one, two, and four; few will lose a child, and almost none will lose a grandchild to COVID-19. In situations where mortality concentrates among the young, however, these caps would not apply and there would be substantial heterogeneity in mortality experiences, between people and potentially between epidemiological realities ( 3 ).…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…An expanding body of literature uses survey data to quantify how different mortality conditions result in experiences of kin death among surviving family members. For example, recent survey-based research shows how all-cause mortality can translate into unequal burdens of familial loss ( 19 ), including specific types of loss from the perspective of parents ( 3 ), siblings ( 9 ), and children ( 31 ). Of course, survey data on family deaths can suffer recall biases associated with social network data collection ( 32 , 33 ) and, unfortunately, survey data on the experience of family death are censored during an ongoing crisis given that some who are currently unaffected will go on to later be affected.…”
Section: Introducing An Indicator: Covid-19 Bereavement Multipliermentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the cost in human lives, a huge emotional burden is associated with these deaths. 17 , 18 There are also enormous financial costs to families and society in general, particularly because young people have attained high levels of education and are gradually entering the labour force.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that exposure to death, especially within the family, is an important form of inequality (Umberson et al, 2017) associated with a range of negative outcomes in later life (Patterson et al, 2020;Fletcher et al, 2013;Doku et al, 2020). While the visibility of studies of the lived experience of death (Alburez-Gutierrez et al, 2021) and the prevalence of bereavement in a population has increased in recent years (Smith-Greenaway and Trinitapoli, 2020;Smith-Greenaway and Weitzman, 2020), no similar empirical studies have been conducted in the context of mortality crises.…”
Section: Excess Mortality and The Lived Experience Of Kin Deathmentioning
confidence: 99%